Kebijakan Pemberantasan Peredaran Narkoba di Indonesia dan Meksiko: Sebuah Studi Perbandingan - Randhi Satria dan Nyphadear Tiara S. A. P. (Indonesian Perspective, 2016)
Many countries are trying to fight against drugs, but it is not easy as drugs have very high economic value. This make the producers and distributors keep struggling to expand their markets for getting larger profits and fulfilling the demand of those markets. Basically, Indonesia and Mexico face the same problem, drugs circulation. Both countries use different approaches which resulted on the different impacts from the implementation. This paper discusses about the implications from those differences on the same policy to fight against drugs.Keywords: Indonesia, Mexico, Drug, Comparison, Policy